Excess properties of binary mixtures containing 1-hexyl-3-methylimidazolim bis(trifluoromethylsulfonyl)imide ionic liquid and polar organic compounds - Emilio J. González (2012)
In this work, densities and speeds of sound of seven binary systems containing the reference IUPAC ionic liquid 1-hexyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide mixed with methanol, ethanol, 1-propanol, 2-propanol, acetone, acetonitrile, and dichloromethane were determined along the whole composition range at several temperatures and atmospheric pressure. Moreover, refractive index was also measured for each binary system, covering the whole composition range, at T = 298.15 K. From these experimental data, excess properties, such as excess molar volumes, excess molar isentropic compressibilities, and excess squared refractive indices were calculated and fitted using the RedlichKister equation. Finally, the effect of the temperature on the excess volume and excess molar isentropic compressibility was also analyzed and discussed.